Subpopulation‐specific patterns of intrinsic connectivity in mouse superficial dorsal horn as revealed by laser scanning photostimulation. (27th March 2013) - Kosugi, Masafumi; Kato, Go; Lukashov, Stanislav; Pendse, Gautam; Puskar, Zita; Kozsurek, Mark; Strassman, Andrew M.
Key points Sensory neurons that detect painful and non‐painful stimulation of body tissues have axons that project to the dorsal horn of the spinal cord, where their terminations are partially segregated into superficial (I–II) and deep (III–IV) dorsal horn laminae, respectively. The dorsal horn contains many excitatory and inhibitory interneurons whose axons synapse on other dorsal horn neurons to enhance or suppress sensory transmission. This study used a localized stimulation technique (laser scanning photostimulation) for high‐resolution mapping of synaptic connections between dorsal horn interneurons, in an in vitro'slice' preparation of the mouse lumbar spinal cord. Some neurons in superficial layers of the dorsal horn have long dendrites that extend ventrally into deeper layers of the dorsal horn, and these neurons can receive excitatory or inhibitory synaptic input from neurons in the deeper layers. These interlaminar connections may be involved in interactions between transmission of signals underlying painful versus non‐painful sensations. Abstract The primary goal of this study was to map the transverse distribution of local excitatory and inhibitory synaptic inputs to mouse lamina I spinal dorsal horn neurons, using laser scanning photostimulation. A sample of lamina II neurons was also studied for comparison. Lamina I neurons received excitatory synaptic input from both laminae I–II and the outer part of III–IV, especially the II/III border region, while the inhibitory input zones were mostly confined within I–II. The excitatory synaptic input zones showed a pronounced medial asymmetry, which was correlated with a matching asymmetry in the dendritic fields of the neurons. Inhibitory input from laminae III–IV was found in a subpopulation of neurons occupying a highly restricted zone, essentially one cell layer thick, immediately below the lamina I/II border, with morphological and physiological properties that were distinct from other laminar populations in the superficial dorsal horn, and that suggest a critical role in interlaminar communication. This subpopulation also received excitatory input from laminae III–IV. Within this subpopulation, inhibitory III–IV input was correlated with the presence of long ventral dendrites. Correlations between the distribution of synaptic input zones and dendritic fields support the concept that interlaminar communication is mediated in part via contacts made onto ventrally extending dendrites of superficial laminae neurons. The results point to the presence of cell type specificity in dorsal horn circuitry, and show how the study of connectivity can itself help identify previously unrecognized neuronal populations.